Perception of green advertisment, attitude and purchase intention towards green product: A study of consumers in Kotakinabalu, Sabah - Helenah Abdul Hatta (2014)
The purpose of this study is to examine the perception of green advertisement on attitude toward consumers purchase intention. The study also examines two different mediating effects on the perception of green advertisement. First is the mediating effect of attitude towards advertisement between the dimension of perception of green advertisement and purchase intention. Second mediator is the effect of attitude towards brand between the dimensions of perception of green advertisement and purchase intention. In this study, the dimensions of perception of green advertisement consist of four dimension attributes ( e.g. credibility, trustworthiness, skepticism and information). A total of 200 respondents are used for the statistical data requirement. Data that collected through questionnaire form using random convenient sampling. The statistical method that adopted in this study is by using the SmartPLS software. Bootstrapping is conducted and from the statistical data that collected show there are mediating effect between attitude towards brand and insignificant relationship between the attitudes towards advertisement. Convergent validity, discriminant validity, cross loading and hypothesis testing is conducted in matter to examine and justify the findings for this study. Contribution to this study divided into two which is the theoretical finding and managerial contribution. Whereas for the theoretical finding that achieve from this study is that previous study does not specialized their research, which are conducted in broader spectrum. But for this thesis research conducted is applied to a more specific perception of green advertisement attributes which are divided into four individual attributes ( credibility, trustworthiness, skepticism and information). Furthermore is the fact that non mediating research had conducted simultaneously on attitude towards the advertisement and attitude towards brand. Additional finding that reach from this mediating effect is that there are no mediating effects between the perceptions on green advertisement in influencing the consumers purchasing intention with attitude towards advertisement. Instead, there are mediating effects between perceptions on green advertisement in influencing consumers purchasing intention with the attitude towards brand. Limitation of the study, implication of the study and future research are also included in this study.